Short- and Long-term Evaluation of Dentin-Resin Interfaces Formed by Etch-and-Rinse Adhesives on Plasma-treated Dentin - Hirata, Ronaldo; Sampaio, Camila; Machado, Lucas S. [UNESP]; Coelho, Paulo G.; Thompson, Van P.; Duarte, Simone; Almeida Ayres, Ana Paula; Giannini, Marcelo (Quintessence Publishing Co Inc, 2016)
Purpose: To investigate the influence of atmospheric pressure plasma (APP) treatment on the microtensile dentin bond strength of two etch-and-rinse adhesive systems, after one week and one year of water storage, and additionally to observe the micromorphology of resin/dentin interfaces under scanning electronic microscopy (SEM). Materials and Methods: The occlusal enamel was removed from third human molars to expose a flat dentin surface. The teeth were then randomly divided into six groups (n = 7), according to two adhesives (Optibond FL and XP-Bond) and three APP treatments (untreated dentin [control], APP application before or after acid etching). After performing the composite resin buildup on bonded dentin, the teeth were sectioned perpendicularly to the bonded interface to obtain beam-shaped specimens (cross-sectional area of similar to 0.9 mm(2)). The specimens were tested in tension until failure after one week and one year of water storage (1.0 mm/min rate). Bond strength data were analyzed by three-way ANOVA and Tukey's post-hoc test (alpha = 0.05%). Bonded beam specimens from each tooth were also prepared for interfacial SEM investigation. Results: At one week, APP treatment applied after acid etching increased the dentin bond strength for XP Bond, while no effect was observed for Optibond FL. After one year, the bond strength of XP Bond decreased in groups where APP was applied after etching. The evaluation time did not influence the bond strength for Optibond FL. Conclusion: One-year evaluation did not show any sign of degradation of interfacial structures in any group. Application of APP to etched dentin combined with a two-step etch-and-rinse adhesive significantly increased bond strength at one week, but the effect was not stable after one year and was adhesive dependent.
Keywords: plasma; microtensile; dentin adhesion